Polimer biodegradable: solusi ramah lingkungan untuk mengatasi pencemaran plastik laut - wijayanti, nurul (Maliki Interdisciplinary Journal, 2025)
Marine plastic pollution is one of the biggest environmental challenges of the 21st century, threatening marine ecosystems and human health. To address this issue, biodegradable polymers (BPs) are considered as potential alternatives that can replace conventional petroleum-based plastics. This review paper examines five recent international journals published between 2020 and 2025, as well as some additional references from relevant related scientific literature. The main focus of this review includes aspects of material design, innovative applications, natural and artificial degradation processes, and environmental impacts of using BPs. References were selectively chosen based on keywords such as “biodegradable polymer”, “marine pollution”, and “bioplastic”, which were taken from highly reputable and peer-reviewed journals. The main findings of this review include the degradation effectiveness of BPs in various environmental conditions (including marine, soil, and industrial compost), the utilization of BPs in the medical field, food packaging, and the ecological, technical, and regulatory challenges that still need to be addressed. The review concludes that while BPs have great potential as a sustainable solution, mass adoption at the global level still requires technology optimization, production cost reduction, and policy support from the government and industry sector.